Trajectory planning of a suspended cable driven parallel robot with reconfigurable end effector. (December 2017) - Barbazza, L.; Oscari, F.; Minto, S.; Rosati, G.
Abstract: In this paper, a new suspended cable driven parallel robot (CDPR) with reconfigurable end effector is presented. This robot has been conceived for pick and place operations in industrial environments. For such applications, the possibility to change the configuration of the cables at the end-effector level is a promising way to avoid collisions with obstacles in the approaching phases, while reducing at the same time the duration of motion in the remaining part of the trajectory. An optimized trajectory planning algorithm is proposed, which implements a pick and place operation in the operational space with dynamic on-line reconfiguration of the end effector. The results on a simplified scenario demonstrate the ability of the system to obtain reduced movement times together with obstacle avoidance. Highlights: Present a novel class of suspended CDPRs with reconfigurable end-effector. Augment the ability to interact with the environment by changing the cables layout. Perform pick and place task in the operational space where obstacles are present. Optimize the trajectory planning with an on-line reconfiguration of end-effector.